THE IMPORTANCE OF ULTRASOUND RESEARCH METHODS IN THE DIAGNOSIS OF PATIENTS WITH PATHOLOGICAL DEFORMITIES OF THE INTERNAL SLEEP ARTERY (World Bulletin of Public Health, 2024)
In the structure of total mortality, cerebrovascular stroke ranks second and is the leading cause of disability in the population. Prevention of stroke and reduction of disability in this disease is possible as a result of work in two directions: the introduction of effective methods of prevention and improvement of the system of medical care for patients using new hightech effective methods of treatment and diagnosis. The need for surgical intervention in patients with pathological deformity implies the presence of clear indications for surgical treatment, primarily on the basis of determining the hemodynamic significance of tortuosity. However, "unlike atherosclerotic lesions, which were the subject of extensive multicenter studies, and as a result of which clear generally accepted conclusions and recommendations were obtained, no such studies have been conducted on the problem of PD of the branches of the aortic arch, and indications for surgical treatment largely continue to depend on the personal opinion of the surgeon and neurologist on this problem."